Immune-checkpoint inhibitors for glioblastoma: what have we learned? - Omuro, Antonio (Arquivos de Neuro-Psiquiatria, 2022)
Background: Glioblastoma, the most common malignant primary brain tumor, remains a lethal disease with few therapeutic options. Immunotherapies, particularly immune checkpoint inhibitors (ICPi), have revolutionized cancer treatment, but their role in glioblastoma is uncertain. Objective: To review the state of immunotherapies in glioblastoma, with an emphasis on recently published ICPi clinical trials. Methods: In this editorial/opinion article, we critically review results of the first generation of trials of ipilimumab, nivolumab and pembrolizumab in glioblastoma, as well as future directions. Results: Expression of PD-L1 is frequent in glioblastoma, ranging from 60-70% of patients. Phase 1 studies of nivolumab with and without ipilimumab, as well as pembrolizumab, showed no new safety concerns in brain tumors, and no neurotoxicity. However, randomized phase 3 trials of nivolumab showed no survival improvements over bevacizumab in recurrent glioblastoma; no role in newly diagnosed disease as a replacement for temozolomide in unmethylated MGMT promoter tumors; and no benefit as an addition to temozolomide in methylated MGMT tumors. However, studies examining post treatment tumor samples have shown signs of increased immunologic response, and occasional long lasting radiographic responses have been seen. A small study of pembrolizumab suggested a potential role as a “neoadjuvant” treatment in resectable recurrent glioblastoma, while other studies are investigating selection of patients with higher mutational burden and novel agents and combinatorial strategies. Conclusion:  Despite initial negative trials, immunotherapy remains of high interest in glioblastoma, and many trials are still ongoing. Improving our mechanistic understanding of the immunosuppression and T cell dysfunction induced by both tumor and the CNS microenvironment remains however crucial for the development of successful immunotherapeutic approaches in this disease.
Keywords: Glioblastoma; Immunotherapy; Immune Checkpoint Inhibitors; Nivolumab; Pembrolizumab